Incidences of Congenital Hyperthyroidism in Neonates Born to Hyperthyroid Women - Zahida Kamal, Habibullah Babar, Shamayal Mandokhel (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thyroid hormones are important not only for the development of the central nervous system of infants but also play a vital role in regulation of various metabolic activities during infancy. Recent advances in literature have identified the risk of congenital hypo-hyperthyroidism in infants whose mother is suffering from hyperthyroidism. Objective: To estimate the incidence of congenital hyperthyroidism in neonate born to hyperthyroid women. Study Design: Prospective cohort study Place and Duration of Study: Department of Gynaecology, Bolan Medical Complex Hospital Quetta from 1st January 2021 to 30th September 2023. Materials and Methods: Five hundred pregnant women who were suffering from hyperthyroidism were enrolled. The complete demographic details, prima, gravida, body mass index, hypertension, comorbidities were entered in a well-structured questionnaire. Each pregnant woman underwent 3cc blood withdrawal for analyzing her thyroid function test and confirmation the hyperthyroidism. Each pregnant woman was followed up to their delivery. Each baby was sent to Baluchistan Institute of Health Science, Quetta for Thyroid stimulating test which was performed through a blood spot pricked from the newborns heal using pricking lancet. The test was performed within 24-72 hours post-delivery. The maternal antibodies were also analyzed from the same blood spot through enzyme linked immune sorbent assay. Those cases which were identified with congenital hyperthyroidism were further treated for complete assessment and treatment at Balochistan Institute of Child Health Service Quetta. Those neonates with high, subclinical or borderline conditions were referred to a repeat test after 3-5 days, 15 days and 30 days after birth for reassessment and follow up. Results: Majority of the pregnant hyperthyroid women were within the age group of 26-40 years with an overall mean age of 27.8±2.85 years. There were 87.6% those women who showed the presence of autoantibodies in them. Out of the total number of singleton deliveries there were 79.6% of the neonates born with normal body weight while 20.4% were found to be underweight. There were three neonates born with hyperthyroidism detected within the first 72 hours of their life. Conclusion: The overall incidence of congenital hyperthyroidism neonates within pregnant women suffering from hyperthyroidism was reported as 0.6%. Keywords: Incidence, Congenital hyperthyroidism, Neonates, Hyperthyroid women